2019
DOI: 10.1111/geb.12889
|View full text |Cite
|
Sign up to set email alerts
|

The resolution‐dependent role of landscape attributes in shaping macro‐scale biodiversity patterns

Abstract: Aim The aim was to assess whether and to what extent the role of local landscape attributes in shaping macroscopic biodiversity patterns is sensitive to spatial and thematic resolutions of land cover data. Location Sub‐Saharan Africa and continental China. Time period Early 21st century. Taxa studied Terrestrial mammals. Methods We conducted spatial and thematic scaling analyses to generate land cover datasets of different spatial (0.3, 0.5, 1.0 and 9.0 km) and thematic (two, three and five classes) resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…The positive relationship between the richness of different bee groups and landscape heterogeneity has been reported (Boscolo et al, 2017;Moreira et al, 2017;Coutinho et al, 2020;Opedal et al, 2020), indicating the importance of landscape diversity for the biological requirements of these pollinators. It is expected that the landscape structure in fine thematic resolutions better explains species richness (Lawler et al, 2004;Qiu et al, 2019).…”
Section: Influence Of Compositional Heterogeneity and Thematic Resolu...mentioning
confidence: 99%
See 2 more Smart Citations
“…The positive relationship between the richness of different bee groups and landscape heterogeneity has been reported (Boscolo et al, 2017;Moreira et al, 2017;Coutinho et al, 2020;Opedal et al, 2020), indicating the importance of landscape diversity for the biological requirements of these pollinators. It is expected that the landscape structure in fine thematic resolutions better explains species richness (Lawler et al, 2004;Qiu et al, 2019).…”
Section: Influence Of Compositional Heterogeneity and Thematic Resolu...mentioning
confidence: 99%
“…Lower thematic resolutions with a small number of cover classes have a more straightforward classification and may aggregate different functional covers, suppressing the necessary level of details to explain biological variables from landscape attributes (Lawler et al, 2004;Marshall et al, 2020). Higher thematic resolutions, on the other hand, result in more detailed mapping of landscape composition and functional covers (e.g., habitat specialists) (Kendall et al, 2011;Liang et al, 2013), increasing the probability to detect associations between biological attributes (e.g., species richness) and landscape structure (Qiu et al, 2019;Marshall et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a cross‐scale link, however, has long been overlooked in macroecology, as seen in a majority of existing studies where landscape attributes (defined as the quantities and configurations of spatially intertwined ecosystems across a landscape) have normally not been taken into account (e.g., Thuiller et al, 2004). This might be attributable, at least in part, to the limitation that global landscape datasets have had too coarse spatial resolutions (Qiu et al, 2019). Indeed, recent analyses based on fine‐resolution global land cover datasets have demonstrated that landscape attributes can provide a substantial fraction of power (in addition to bioclimatic variables) for explaining terrestrial species richness patterns at regional and continental scales (Martins et al, 2014; Qiu et al, 2019; Xu et al, 2014), and therefore landscape factors should not be excluded a priori for a complete understanding of macroecological determinants.…”
Section: Introductionmentioning
confidence: 99%
“…This might be attributable, at least in part, to the limitation that global landscape datasets have had too coarse spatial resolutions (Qiu et al, 2019). Indeed, recent analyses based on fine‐resolution global land cover datasets have demonstrated that landscape attributes can provide a substantial fraction of power (in addition to bioclimatic variables) for explaining terrestrial species richness patterns at regional and continental scales (Martins et al, 2014; Qiu et al, 2019; Xu et al, 2014), and therefore landscape factors should not be excluded a priori for a complete understanding of macroecological determinants. Beyond the complementary benefits, these findings help to bridge landscape ecology and macroecology, which are two important, but largely unconnected fields.…”
Section: Introductionmentioning
confidence: 99%